Interocular Asymmetry of Foveal Thickness in Parkinson Disease. (1st August 2012) - Shrier, Eric M.; Adam, Christopher R.; Spund, Brian; Glazman, Sofya; Bodis-Wollner, Ivan
Abstract : Purpose . To quantify interocular asymmetry (IA) of foveal thickness in Parkinson disease (PD) versus that of controls. Design . Prospective case-control series. Methods . In vivo assessment of foveal thickness of 46 eyes of 23 PD patients and 36 eyes of 18 control subjects was studied using spectral domain optical coherence tomography (SD-OCT). Inner versus outer layer retinal segmentation and macular volumes were quantified using the manufacturer's software, while foveal thickness was measured using the raw data from each eye in a grid covering a 6 by 6 mm area centered on the foveola in 0.25 mm steps. Thickness data were entered into MATLAB software. Results . Macular volumes differed significantly at the largest (Zone 3) diameter centered on the foveola (ETDRS protocol). By segmenting inner from outer layers, we found that the IA in PD is mostly due to changes on the slope of the foveal pit at the radial distances of 0.5 and 0.75 mm (1.5 mm and 1 mm diameter). Conclusions . About half of the PD patients had IA of the slope of the foveal pit. IA is a potentially useful marker of PD and is expected to be comparable across different SD-OCT equipment. Data of larger groups may be developed in future multicenter studies.